Pengaruh leverage, audit tenure dan ukuran perusahaan terhadap integritas laporan keuangan pada perusahaan sektor industri dasar dan kimia di BEI - Marselin Pangi; Priscillia Weku (Yayasan Widyantara Nawasena Raharja, 2023)
The integrity of financial reporting refers to the accuracy and honesty with which financial information is presented. It is essential that all information about the company's financial position, performance and cash flows is accurate and reflects the company's circumstances, as the company is accountable to the users of financial reports, including investors and creditors. The integrity of financial reports is assessed using the market-to-book ratio, which measures the difference between the company's assessment and the market. This study aims to investigate the effects of leverage, audit tenure, and firm size on the integrity of financial reports through quantitative research. This research analyses the financial statements of Basic Industry and Chemical Sector companies listed on the IDX for the period of 2019-2021, using purposive sampling techniques and secondary data. Multiple linear regression analysis was conducted for estimating the relationship among variables. The findings indicate that leverage does not affect the integrity of financial statements, while audit tenure has a significant impact on the integrity of financial statements. Additionally, the study found that company size has a negative and significant effect on the integrity of financial statements.